Subject, Interest, and Community in Lynn Nottage's Sweat and Dominique Morisseau's Skeleton Crew. - Keramatfar, Hossein (Neophilologus, 2024)
This paper studies two contemporary plays, Lynn Nottage's Sweat (2015) and Dominique Morisseau's Skeleton Crew (2017), and contends that they examine the assumption that the neoliberal ideology can be effectively confronted through a critical examination of the subject of neoliberalism. It draws mainly upon Foucault's discussion of neoliberalism and Wendy Brown's thoughts about the neoliberal society and argues that the subject that neoliberalism constructs and privileges, homo economicus, is motivated merely by economic gain and seeks to maximize his/her interests in a competitive environment with restricted resources. Sweat and Skeleton Crew, this paper suggests, point to the social immolation that the dominance of the neoliberal subjectivity brings about. They both also highlight the point that marginalized population is especially vulnerable to the principles of the neoliberal ideology. They, therefore, emphasize the need to confront neoliberalism through encouraging altruistic tendencies which requires abandoning the homo economicus model of human behavior.